METODE SQ3R DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPS TERPADU - Anita Fikti Utami; Tedi Rusman; Yon Rizal (FKIP Unila, 2016)
The purpose of this study was to determine the effect of the SQ3R (Survey, Question, Read, Recited, Review) method and the motivation against the learning outcomes. The population in this research was all class of VIII of SMP as much as five classes with the number of 183 students. The sample in this study was 126 students from the entire population has the same chance to be selected into the sample. The technique of collecting data was through observation, questionnaires, documentation and testing. Hypothesis testing was using partial test (on their own) and a simultaneous test (simultaneously / together). The results showed: (1) There is an effect of SQ3R methodsof Integrated Social Science, (2) There is an effect of learning motivation for learning outcomes of Integrated IPS, (3) There is an effect of SQ3R methods and learning motivation on learning outcomes of Integrated IPS.Penelitian ini bertujuan untuk mengetahui pengaruh metode SQ3R (Survey, Question, Read, Recited, Review) dan Motivasi Belajar Terhadap Hasil Belajar. Populasi dalam penelitian ini adalah seluruh kelas VIII SMP sebanyak 5 kelas dengan jumlah 183 siswa. Sampel dalam penelitian ini adalah 126 siswa dari seluruh populasi yang memiliki kesempatan sama untuk dipilih menjadi sampel. Teknik pengumpulan data melalui observasi, kuisioner / angket, dokumentasi dan tes. Pengujian Hipotesis menggunakan uji parsial (sendiri-sendiri) dan uji simultan (serentak/bersama-sama). Hasil penelitian menunjukkan : (1) Ada pengaruh metode SQ3R terhadap hasil belajar IPS Terpadu, (2) Ada pengaruh motivasi belajar terhadap hasil belajar IPS Terpadu, (3) Ada pengaruh metode SQ3R dan motivasi belajar terhadap hasil belajar IPS Terpadu.Kata kunci: hasil belajar, metode SQ3R, motivasi belajar